Assessing the Fiscal Costs and Benefits of A8 Migration to the UK - Christian Dustmann; Tommaso Frattini; Caroline Halls (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
This paper assesses the fiscal consequences of migration to the UK from the Central and Eastern European countries that joined the EU in May 2004 (A8 countries). We show that A8 immigrants who arrived after EU enlargement in 2004, and who have at least one year of residence - and are therefore legally eligible to claim benefits - are 60% less likely than natives to receive state benefits or tax credits, and 58% less likely to live in social housing. Even if A8 immigrants had the same demographic characteristics of natives, they would still be 13% less likely to receive benefits and 28% less likely to live in social housing. We then compare the net fiscal contribution of A8 immigrants with that of individuals born in the UK, and find that in each fiscal year since enlargement in 2004, A8 immigrants made a positive contribution to public finance despite the fact that the UK has been running a budget deficit over the last years. This is because they have a higher labour force participation rate, pay proportionately more in indirect taxes, and make much lower use of benefits and public services.
Keywords: J61; H20; 330; Migration; Fiscal Impact; Welfare state